A method to determine the ozone radiative forcing in the ultraviolet range from experimental data. Issue 4 (27th February 2014) - Antón, M.; Mateos, D.; Román, R.; Valenzuela, A.; Alados‐Arboledas, L.; Olmo, F. J.
Abstract This paper proposes a method to calculate the ozone radiative forcing (RF) at surface in the ultraviolet (UV) spectral range for all‐sky conditions based on the estimation of the ozone efficiency (OE) from experimental data that are subsequently applied to changes on the total ozone column (TOC) since late 1970s. The OE is defined as the rate at which the solar UV irradiance is "forced" per TOC unit, being estimated for all‐sky conditions from UV‐B (280–320 nm) and TOC data recorded with a Bentham spectroradiometer at Granada (Spain). The results showed a clear seasonal pattern in the OE values with largest monthly averages (in absolute terms) in July (−4.2 ± 0.3 mW/m2 per Dobson Unit) and the smallest in January (−0.7 ± 0.3 mW/m2 per Dobson Unit). The continuous and consistent TOC data set (1979–2008) provided by the Multisensor Reanalysis over the study site showed that spring months present the largest annual TOC changes relative to 1979 while summer months exhibit small variations. Thus, spring has the largest contribution ( 53%) to annual ozone RF followed by summer ( 17%), winter ( 16%), and autumn ( 4%). The evolution of the ozone RF relative to 1979 in the UV‐B range at Granada showed positive values for most of years (between 5 and 40 mW/m2). Finally, the long‐term evolution of the ozone RF exhibited a positive trend until the mid‐1990s and, subsequently, a weak negative trend until the end of the analyzed period.